Association between weekend admission and in-hospital mortality for patients with ischemic heart disease upon surgery treatment - Liu, Tianzhao; Lin, Chuangpeng; Jia, Chenyang; Wu, Binbin; Liu, Hailong; Liang, Yan (Frontiers in Cardiovascular Medicine, 2024)
Background The existence and reasons for the weekend effect in patients with ischemic heart disease (IHD) were not yet fully identified. This study aimed to evaluate whether weekend admission was independently associated with in-hospital mortality and the possible mechanisms associated with the IHD patients. Methods The study was a retrospective study, including IHD patients from 2015 to 2023. The International Classification of Diseases, tenth revision (ICD-10) codes were used to identify all admissions with a primary diagnosis of IHD. The sample was divided into weekday and weekend groups. We performed a multivariate logistic regression analysis and a mediation analysis to estimate the effect of weekend admission on hospital mortality. Results A total of 18,906 IHD patients were included in the study, with an average age of 63.8 ± 12.7. Of these patients, 21.7% (n = 4,102) were admitted over the weekend. The in-hospital 30-days mortality rate was significantly higher among the patients admitted at weekends compared with those admitted at weekdays (2.0% vs. 1.1%). Respectively, the 30-day mortality rate of patients admitted on weekends was higher compared to patients admitted on weekdays among patients with surgical treatment (2.34% vs. 1.06%, OR = 1.75; 95% CI: 1.23–2.42) and with emergency admission (3.48% vs. 2.59%, OR = 1.56; 95% CI: 1.05–2.28). Mediation analyses showed that the surgical scheduling had significant mediated effects on the associations of admission time with mortality risk. Conclusions IHD patients with a surgical therapy or admitted from emergency department had a significantly higher risk of mortality when admitted on weekends compared to weekdays. These findings have potential implications for resource allocation and redistribution of surgery to weekends in hospitals.